Evolution of Two Major Zika Virus Lineages: Implications for Pathology, Immune Response, and Vaccine Development - Beaver, Jacob T.; Lelutiu, Nadia; Habib, Rumi; Skountzou, Ioanna (Frontiers in Immunology, 2018)
Zika virus (ZIKV) became a public health emergency of global concern in 2015 due to its rapid expansion from French Polynesia to Brazil, spreading quickly throughout the Americas. Its unexpected correlation to neurological impairments and defects, now known as congenital Zika syndrome, brought on an urgency to characterize the pathology and develop safe, effective vaccines. ZIKV genetic analyses have identified two major lineages, Asian and African, which have undergone substantial changes during the past 50 years. Although ZIKV infections have been circulating throughout Africa and Asia for the later part of the 20th century, the symptoms were mild and not associated with serious pathology until now. ZIKV evolution also took the form of novel modes of transmission, including maternal-fetal transmission, sexual transmission, and transmission through the eye. The African and Asian lineages have demonstrated differential pathogenesis and molecular responses in vitro and in vivo. The limited number of human infections prior to the 21st century restricted ZIKV research to in vitro studies, but current animal studies utilize mice deficient in type I interferon (IFN) signaling in order to invoke enhanced viral pathogenesis. This review examines ZIKV strain differences from an evolutionary perspective, discussing how these differentially impact pathogenesis via host immune responses that modulate IFN signaling, and how these differential effects dictate the future of ZIKV vaccine candidates.